Legislative regulation of administrative services in the conditions of martial law - DYNNYK Ірина (Ius Modernum, 2024)
In wartime, the prompt provision of high-quality services in the field of state registration of civil status acts is extremely important. In order to improve the quality and accessibility of the provision of administrative services in the field of state registration of civil status acts in the conditions of martial law, it is appropriate to study the urgent problems that arise during the provision of services. The purpose of the article is to substantiate the main instruments of legislative regulation of the provision of administrative services under martial law. The presented study is based on the hypothesis of the need to study the general aspects of the provision of administrative services in Ukraine, as well as the direction of electronic administrative services. To achieve the goal, the following research methods were used: historical, logical, statistical analysis, synthesis and comparison, generalization. It was determined that many theoretical provisions on administrative services are still controversial, which to some extent inhibits their legislative support. However, without legislative improvement, it is impossible to talk about their effective practical implementation. Improving the provision of electronic services in wartime requires a comprehensive approach to ensure reliability, availability and security. The war significantly affected the work of administrative service centres. Thus, from the first day of the full-scale invasion, the provision of administrative services in the centres was suspended. Most of the services provided by the centres require the implementation of measures specified in the relevant state registers. It was determined that the declaration of martial law in 2022 requires an urgent review and adaptation of the legislation on the provision of administrative services. Effective governance in this context requires flexibility, innovation and response to rapid changes, particular attention to the needs of the population.